Measuring the skills and psychological readiness of female teachers towards employing computers in the educational process in Riyadh - Al-Qahtani, Alia Abdulaziz Al Amer (Journal of Educational and Psychological Sciences, 2020)
This study aimed to identify female teachers’ skills readiness towards applying Computer Technology in Educational Process in Riyadh and their psychological readiness result from training and practice, and to highlight the most prominent difficulties which lead to reduce the level of applying computer for female teachers in educational process (quantitatively and qualitatively) and to provide proposals to increase its effectiveness. In order to achieve this goal, the researcher used the descriptive method. The study sample consisted of 243 female teachers of general education in Riyadh who was selected randomly. The most prominent results that the study sample was agreed with a high degree towards: (psychological readiness of female teachers to apply the computer in educational process, impact of applying computer in education on female teachers with an arithmetic mean (2,6 of 3) and (2.74 of 3) respectively. While they were agreed with a medium degree towards: (skills readiness of female teachers to apply computer in educational process, difficulties face female teachers to apply computer in education process) with an arithmetic mean (2,05 of 3) and (2,21 of 3) respectively. The most prominent programs which were applied are: display program and search engines. The study results indicated that there are statistically significant differences between the average responses of the study sample towards the psychological readiness of female teachers towards applying computer in the educational process, according to variable of training programs.